The Role of Arbuscular Mycorrhizal Fungus (Gigaspora margarita) on Mercury and Nutrients Accumulation by Enterolobium cyclocarpum Seedlings - HANNA ARTUTI EKAMAWANTI; YADI SETIADI; DIDY SOPANDIE; DWI ANDREAS SANTOSA (Indonesian Society for microbiology, 2013)
A river-sand culture experiment was conducted to investigate whether arbuscular mycorrhizal (AM) colonization influenced mercury (Hg) and nutrients accumulation, and whether AM fungus (AMF) Gigaspora margarita enhance host plant sengon buto (Enterolobium cyclocarpum) tolerance to Hg. Hg was applied as HgCl2 at different levels (375 and 750 µM) and added to the full strength of Hoagland's solution, then applied to seedlings in river-sands as growth media according to treatments. The non-mycorrhizal and mycorhizal E. cyclocarpum roots took up Hg, but its translocation to the leaves was inhibited. AM inoculation decreased significantly Hg content of roots seedlings by 70.5% from non-AM inoculation seedlings. Mycorrhizae enhanced significantly Ca and Mg uptake in shoot by 1.29- and 1.27-fold higher than non-mycorrhizal seedlings, but not enhanced significantly P uptake. Based on the roots dry weight, the tolerance index of non-mycorrhizal or mycorrhizal seedlings treated with 750 µM Hg supply was > 50%. It indicated that the seedlings can tolerate up to 750 µM Hg added. Considering the possible differences in AMF response to Hg in polluted soil from the field, it is not yet clear if Gi. margarita could be applied for phytoremediation of Hg in contaminated sites. Therefore, more work needs to be done using AMF isolates to reveal the possible application in the management of Hg contaminated soils.